(untitled) (Journal of Applied and Natural Science, 2015)
Among, six modules tested against Helicoverpa armigera on tomato, the IPM module I consisting interspersing of 1 row of african marigold after every 8 rows of tomato as well as on the periphery of the plot and spray of neem based formulation gromin 1 % EC @ 0.5 ml /l on appearance of the first instar larvae.IPM module II was interspersing of 1 row of african marigold after every 8 rows of tomato as well as on the periphery of the plot spray of neem based formulation gromin 1 % EC @ 0.5 ml /l on appearance of the first instar larvae and two spray of HaNPV @ 350 LE/ha alternated with neem oil @ 0.5 % + 0.1 % soap solution.IPM module III consisting interspersing of 1 row of african marigold after every 8 rows of tomato as well as on the periphery of the plot and two spray of Beauvaria basiana @ 40g/10 l at appearance of first instar larvae alternated with Nikuchhi @ 1.0 %. and IPM module IV are growing of african marigold after every 8 rows of tomato as well as on the periphery of the plot and two spray of HaNPV @ 350 LE/ha on appearance of first instar larvae followed by spray of Decidan 32.8% EC @ 15ml/10 litre. The IPM module V was alternate spray of Polytrin c 44 % EC @ 10ml/10 litre on appearance of first instar larvae and subsequent spray at 15 days intervals and Module VI was Control. IPM-IV module was found highly effective and economical for management of tomato fruit borer, Helicoverpa armigera and it exhibited least tomato fruit borer damage (3.44%) and maximum tomato yield (257.25q/ha). This research gave the best result to farmers for the control of H. armigera in tomato crops.